Meningkatkan kemampuan berfikir kreatif siswa Sekolah Dasar melalui model brain jogging - Willy Ihsan Rizkyanto; Wawan Sundawan Suherman; Hari Yuliarto; Ismail Gani; Dhani Priantoro (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
Penelitian ini bertujuan menguji perbedaan pengaruh model pembelajaran berbasis Brain jogging dengan model konvensional/direct instruction dalam meningkatkan kemampuan berfikir kreatif peserta didik Sekolah dasar. Studi ini adalah studi quasi eksperimenal dengan kelompok kontrol. Sampel dalam penelitian ini adalah peserta didik kelas atas yaitu kelas 4-6. Teknik Sampling yang digunakan adalah simple random sampling. Peneliti mengambil kelas pararel kelas 4A dan 4B untuk ditetapkan masingmasing sebagai kelompok eksperimen dan kelompok kontrol. Sampel kelompok eksperimen dan kontrol berjumlah 30 siswa dimana karakteristik keduanya sama. Berdasarkan data kelas eksperimen didapat jumlah sampel yang valid 30 skor 48.40 ± 2.931. Sedangkan kelas Experimentl didapat jumlah sampel yang valid 30 skor 49.57 ± 2.979. Pada perolehan data pre-test kelas kontrol didapat jumlah sampel yang valid 30 skor 38.7 ± 6.607. Sedangkan data post test kelas kontrol didapat jumlah sampel yang valid 30 skor 39.43 ± 6.796. Berdasarkan uji uji hipotesis dengan perhitungan Man Whitney diperoleh nilai sig (2tailed) sebesar 0,0000,05. Dapat disimpulkan kelas experiment dengan treatment model pembelajaran brain jogging lebih baik jika dibandingkan dengan model konvensional/direct instruction dalam meningkatkan kemampuan berfikir kreatif.Develop children's creative thinking skills in elementary school with the brain jogging modelAbstractThis study aims to examine the differences in the influence of the Brain jogging-based learning model with the conventional/direct instruction model in improving the creative thinking skills of elementary school students. This study is a quasi-experimental with a kontrol group. The sample were upper class students (grades 4-6). The sampling technique used is simple random sampling. The researcher took parallel classes 4A and 4B to designate each as the experimental group and the kontrol group. The sample of the experimental and kontrol groups totaled 30 students where the characteristics of both were the same. Based on experimental class data, the number of valid samples was 30 with a score of 48.40 ± 2.931. While the Experimental class obtained a valid sample size of 30 with a score of 49.57 ± 2.979. In obtaining pre-test data for the kontrol class, the number of valid samples obtained was 30 with a score of 38.7 ± 6,607. Meanwhile, the post-test data for the kontrol class obtained a valid sample size of 30 with a score of 39.43 ± 6.796. Based on the hypothesis test using Man Whitney calculations, a sig (2 tailed) value is 0.000 0.05. It can be concluded that the experimental class with the treatment of the brain jogging learning model is better when compared to the conventional/direct instruction model in improving creative thinking skills.